PENGUKURAN EFEKTIVITAS IKLAN (STUDI KOMPARASI: IKLAN MEDIA CETAK DAN IKLAN MEDIA ONLINE): Lasmery RM Girsang - Jurnal COMMED (Commed : Jurnal Komunikasi dan Media, 2017)
The shift in advertising in the media have change of strategy in terms of providing for the cost of the ad campaign products/services providers who make the company had to think hard to be able to introduce products / services that attract public attention. Therefore, quantitative research based Theory Usability and Satisfaction (Uses and Gratification Theory) will measure the effectiveness of ads (a comparative study: print ads and online media advertising) by mapping the EPIC model of the 111 respondents in Jakarta. The results were as follows: (1) The average scores for the dimension Empathy magazine ad for 3,74, while on youtube of 3.6; (2) The average scores for the dimensions of Persuasion advertisement in a magazine of 3.60 while on youtube of 3.45; (3) The average scores for the dimensions of the ad in the magazine Impact 3,82 while on youtube by 3, 765; (4) The average scores for the dimensions of a magazine ad Communication of 3.85 while on youtube of 3.84; and (5) EPIC magazine advertising rate of 3.75 while on youtube of 3.67.